The Role of Micro Small and Medium Enterprises (MSMEs) in the Recovery of the National Economic - Ikhsan Lubis (Magister Ilmu Hukum Fakultas Hukum Universitas Syiah Kuala, 2021)
The application of Micro, Small and Medium Enterprises (MSMEs) has a considerable influence in contributing and developing as the main supporter in the implementation of National Economic Recovery (NER) programs. This paper leads to a qualitative descriptive approach. This research has been developed using a literature review approach. This conceptual approach is carried out by referring to sources, namely books, journals and the internet.” The research design uses descriptive qualitative which can be interpreted that a series of activities aimed at getting the results of the research as it is at the conclusion. problems that exist with existing policies in order to realize the program from (NER) and as a result of the Covid19 pandemic, there are still some obstacles and problems in the protection and empowerment of cooperatives and MSMEs.